Pandemic, but Make It Fashion: Ukrainian Embroidered PPE in the Time of COVID-19 - Chomitzky, Katya (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2021)
Embroidered pandemic wear has become one of the newest cultural fashion trends to emerge in Ukraine and within its Canadian diaspora. This article explores the ways in which embroidery as a traditional form of culture retains meaning within modern contexts, while also serving as a vehicle for experimenting with atypical applications of cultural symbols and representations. Throughout the COVID-19 pandemic, cloth masks have been recommended by public health officials, including the World Health Organization, as a preventative measure to limit the spread of the virus. On the basis of digital fieldwork, I discuss the meanings and inspirations behind these embroidered masks, while conducting a material culture analysis of the objects themselves. I argue that, through a subversion of their common purpose— to hide one’s identity— masks have been used in the pandemic as an open/performative display of culture. I contend that this display acts as a means to promote tradition through ephemera and assert cultural importance. This, coupled with the personal/private use of embroidery as a protective talisman, has fueled a trend of embroidered personal protective equipment in popular culture. In this article, I examine the purpose, use, and form of these masks in order to bring light to the ways in which cultural traditions and objects act (and developed prevalence) as a form of pandemic response.